USING OF ER:YAG LASER FOR VESTIBULOPLASTY IN THE LOWER JAW - Gerasimova Pishevska, Sofijanka; Simjanovska, Ljuba; Markovska Arsovska, Mirjana; Peeva Petreska, Marija; Chadikovska, Elizabeta (Macedonian Association of Anatomists and Morphologists, 2019)
The main aim of this case report was to evaluate the effect of Er:YAG laser-assisted vestibuloplasty and postoperative outcomes of this surgical technique in a patient with inadequate deepness in the oral vestibulum. In this case we present the use of Er:YAG laser to change the soft tissue attachments in the oral vestibulum of the lower jaw. A 59-year-old patient was referred to the University Department of oral surgery. Intraoral clinical examination showed complete mandibular edentulism with inadequate deepness of vestibulum, sufficient bone height in anterior region and presence of mucosal ligaments. Anterior mandible vestibuloplasty was planned to prepare the patient for prosthetic rehabilitation. The patient was operated on using laser assisted technique for vestibuloplasty with Er:YAG laser (Fotona Fidelis III) to deep the oral vestibulum. Er:YAG laser-assisted vestibuloplasty is a minimally invasive surgical procedure with no pain and bleeding. Preprosthetic surgery of the vestibule accomplished with laser beam offers favorable clinical results during and after the operation. Advantages of laser treatment over conventional methods include minimal cellular destruction, tissue swelling and scarring, hemostasis, minimal or no suturing, reduction in surgical time, postoperative pain and discomfort.
Keywords: Preprosthetic surgery; Er:Yag laser; vestibuloplasty